(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article explores the compositional structure and narrative characteristics of Karakalpak folk fairy tales. It highlights the unique features of oral folklore, including the simplicity and accessibility of plot lines, the use of traditional introductions, and the flexible narrative structure that often begins with central conflicts rather than chronological exposition. It also examines the influence of humor, imaginative elements, and formulaic expressions in shaping the tales’ aesthetic appeal. Furthermore, the role of traditional storytellers and the evolution of fairy tale narration in Karakalpak society is discussed, illustrating the oral tradition’s adaptability and enduring cultural significance.